Visualizing order in dispersions and solid state morphology with Cryo-TEM and electron tomography: P3HT : PCBM organic solar cells1. Issue 9 (7th March 2015) - Wirix, Maarten J. M.; Bomans, Paul H. H.; Hendrix, Marco M. R. M.; Friedrich, Heiner; Sommerdijk, Nico A. J. M.; de With, Gijsbertus
<x xml:space="preserve">Abstract</x> Building blocks for organic solar cells are made from P3HT in a P3HT : PCBM solution in toluene and used to tune the morphology of the photoactive layer.